2020
DOI: 10.1101/2020.06.11.20128280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostic accuracy of the 4AT for delirium detection: systematic review and meta-analysis

Abstract: Objective: Detection of delirium in hospitalised older adults is recommended in national and international guidelines. The 4 'A's Test (4AT) is a short (<2 min) instrument for delirium detection that is used internationally as a standard tool in clinical practice. We performed a systematic review and meta-analysis of diagnostic test accuracy of the 4AT for delirium detection. Methods: We searched MEDLINE, EMBASE, PsycINFO, CINAHL, clinicaltrials.gov and the Cochrane Central Register of Controlled Trials, f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The four items are alertness, cognition (a short test of orientation), attention (recitation of the months in backwards order), and the presence of acute change or fluctuating course. A meta-analysis of 17 diagnostic test accuracy studies (n = 3,701 observations) reported a pooled sensitivity and specificity of 88% 217 . In a randomized controlled trial, the 4AT had higher sensitivity than and similar specificity to the CAM 208 .…”
Section: Assessment Of Episodic Delirium In Non-icu Settingsmentioning
confidence: 99%
“…The four items are alertness, cognition (a short test of orientation), attention (recitation of the months in backwards order), and the presence of acute change or fluctuating course. A meta-analysis of 17 diagnostic test accuracy studies (n = 3,701 observations) reported a pooled sensitivity and specificity of 88% 217 . In a randomized controlled trial, the 4AT had higher sensitivity than and similar specificity to the CAM 208 .…”
Section: Assessment Of Episodic Delirium In Non-icu Settingsmentioning
confidence: 99%
“…A rapid screening tool for delirium is the 4 AT which may take only 2 min to do. The 4AT is a well-validated tool that shows good diagnostic accuracy with a pooled sensitivity of 0.88 (95% CI 0.80 to 0.93) and pooled specificity of 0.88 (95% CI 0.82 to 0.92) in older (≥ 65 years) people in various care settings that include emergency department, medical, stroke and surgical wards [18]. Precipitating factors for delirium such as sleep deprivation, pain, constipation and urinary retention should be avoided or promptly treated as possible.…”
Section: Acute Carementioning
confidence: 99%
“…88 (95% CI 0.80 to 0.93) and pooled specificity of 0.88 (95% CI 0.82 to 0.92) in older (≥ 65 years) people in various care settings that include emergency department, medical, stroke and surgical wards. [24] The 4AT has some advantages over other screening tools such as the Acute Confusion Method (CAM) as being shorter, simpler and not requiring special training for the operator. [24] The 4AT is designed to be used by any health care professional at the first contact with patient and at follow-up at any time when delirium is suspected (Table 3).…”
Section: Screening and Diagnosismentioning
confidence: 99%